Kepemimpinan nasional dan dinamika lembaga perwakilan rakyat - Mahendra A.A. Oka, 1946- (Pedungan, Denpasar : Pustaka Manikgeni, 1997)
National leadership, the presidency, and role of Indonesia's legislative body; articles
Keywords: Indonesia. -- Dewan Perwakilan Rakyat; Political leadership -- Indonesia; Indonesia -- Politics and government -- 1966-1998